KERAGAMAN GENETIK KELAPA DALAM MAPANGET NOMOR 32 HASIL PENYERBUKAN SENDIRI BERDASARKAN PENANDA RAPD - HENGKY NOVARJANTO; J. KUMAUNANG; M. A. TULALO; A. MASNIAWATI; A. HARTANA (Pusat Penelitian dan Pengembangan Perkebunan, 2001)
Genetic variability of selfing Mapanget Tall coconut No. 32 based on RAPD markerThe objective of this study was to analyze the genetic variability of seling Mapanget Tall coconut No. 32 used RAPD marker. Ihe method of morphology, fruit component and isozymc analyses could not explain the homozygote level of the offspring and his parents. The DNA analysis was done at Plant Biology Laboratory, PAU, Life Science IPB, and the coconut leaflets samples were collected from Kima Atas Research Instalation, Research Institute for Coconut and Palmae, Manado. This research the study was conducted from November 1999 to Fcbruay 2000. Coconut materials analyzed were DMT 32-OP, DMT 32-S2, DM 1 32-S3 andDMT32-S4. DMT 32-S2 was the offsprings of the selfcd DMT 32- SI coconut seling. and the DMT 32-SI came from the sclfed of DMT 32-OP. Then selfcd DMT 32-S2 produced were found the DMT 32-S3. and selfcd of DMT 32-S3 produced the progeny of DMT 32-S4. DNA was isolated using the method of ROHDE et at (1995), while DNA quantity and quality was using the method of SAMBROOK et al (1989). Then the DNA was ampliied using 10 random primer 10 mer and PCR apparatus of 2.400 Perkin-Elmer System. Ater thai the DNA was elcctrophorated, and photographed using Polaroid 667 ilm, then ihe biner data matrix of each coconut population was calculated lor Ilic number of monomorphism banding was found in DMT 32-S2. Ihe genetic similarity between DMT 32-S3 and DMT 32-S3 was the mosl similar at genetic distance of 90%. DMT 32-S3 resulted from self pollination can be recommended as parent material for hybridization.